Context of Institutional Trust Erosion: An Inquiry into Workers' Experiences in Accessing Support and Welfare Institutions - Mohadeseh Zia Naserani; Hossein Afrasiabi; SeyedAlireza Afshani; Hamid Ebadollahi-Chanzanagh (Strategic Research on Social Problems)
IntroductionOne of the fundamental components of social capital is the level of social or institutional trust. Institutional trust emerges when citizens perceive government institutions as accountable, efficient, benevolent, predictable, open, transparent, fair, and honest. It represents an abstract form of trust placed in institutions and organizations. The degree of trust individuals have in different institutions varies across societies and evolves over time. People anticipate that each organization will act in alignment with its foundational goals and nature. Consequently, if an organization fails to act according to its defined objectives, it will lose its efficacy. The effectiveness or ineffectiveness of an organization, as perceived by different individuals in the society, influences the legitimacy or illegitimacy of that organization in their eyes. This, in turn, shapes people's level of trust in these institutions. Examining workers' experiences with welfare and social security institutions, such as Labor Department, Cooperatives and Social Welfare, and Social Security Organization, can be of great significance in comprehending the acceptance, legitimacy, or illegitimacy of these institutions from the workers' perspective. Therefore, the aim of the present study was to investigate workers' experiences when interacting with these institutions. In doing so, we sought to address the following questions: How do workers feel when they visit these institutions? To what extent do they perceive these institutions as facilitators? What has been their interaction with the staff of these supportive institutions? How do they evaluate the efficiency of these institutions? And are they inclined to revisit them to resolve their issues?   Materials & MethodsIn this exploratory study, a constructivist grounded theory approach rooted in the interpretive-critical paradigm was employed. The researchers assumed multiple roles, including that of a worker, researcher, and employee of one of the supportive institutions in the field, to gather the necessary data.In the initial stage, one of the researchers immersed themselves in the role of a worker, adopting a covert and non-systematic observation approach within a natural setting to collect data. This involved actively participating in the worker's role and observing the environment.The second stage involved the researchers assuming their actual roles as researchers in workshops and supportive welfare institutions. Through interactions with workers, techniques, such as semi-structured interviews, were conducted and the researchers attended dispute resolution sessions between workers and employers at Tehran Province Cooperatives, Labor, and Social Welfare Administration.The third stage involved one of the researchers assuming the position of an employee in a relevant supportive institution, specifically the Social Security Organization. By becoming a complete participant in the research field, the researcher aimed to gain a deeper understanding of the workers' level of trust in welfare and supportive institutions, as well as the nature of their interactions with these institutions. Similar to the first stage, information was collected through covert and non-systematic observation within a natural setting.Participant selection was done through a purposive and theoretical sampling approach. The sample consisted of unemployed Iranian workers living in Tehran, who were accessed through referrals to the Labor, Cooperatives, and Social Welfare Administration, as well as the Social Security Organization. The number of participants continued until theoretical saturation was achieved, adhering to the principles of qualitative sampling. Theoretical and analytical field notes provided a comprehensive understanding of the research context. These notes aided in uncovering covert policies, capturing insights that could not be extracted solely through worker interviews, and facilitated the comprehension of the underlying relationships between agents of supportive institutions and workers. The enrichment of categories, the strengthening of relationships between concepts and categories, and the inclusion of 37 workers with workshop experience ultimately led to theoretical saturation. Discussion of Results & ConclusionInstitutional distrust is a form of distrust that exists at intermediate levels within the society. It pertains to the lack of trust in organizations, administrations, and various types of institutions in the society. These organizations and institutions serve as intermediaries between the broader governing system at the macro level and the interactions between individuals at the micro level. They are established as a result of macro-level policymaking and their existence is shaped and sustained through the actions of individuals at the micro level, while also being influenced by conflicts between actions and reactions. Our analysis of the interviewees' narratives led us to a different conclusion regarding institutional trust and the factors that enhanced or undermined it compared to the existing discussions. While Claus Offe argues that institutional trust is contingent upon the performance of organizational agents and actors, our analysis of the interviewees' narratives suggested that institutional distrust could be examined at two levels: agency and structure. This level of analysis aligned with Sztompka's analysis of institutional distrust.The difference in the findings of our study did not lie in the level of analysis, but rather in the specific factors influencing each level of analysis. It appeared that institutional distrust arose from the actions of implementers and institutional agents within the dominant institutions, as well as the structure of the institutions themselves. At the agency level, visitors' negative experiences with agents and institutional intermediaries, including encounters with administrative, financial, and moral corruption, lack of empathy from intermediaries, and bureaucratic obstacles that hindered the exercise of individual rights, along with nepotism and a management style reminiscent of tribalism, contributed to the prevalence of institutional distrust among the public.Since institutional distrust at the agency level often contradicts the underlying philosophy and goals of institutions and organizations, it tends to be more concrete and observable and has received more attention. Visitors are generally more aware of this level of institutional distrust. Moreover, institutional distrust at the agency level is more amenable to reform.However, a more abstract and intangible form of institutional distrust exists at the structural level. Each institution has its own social objectives and goals. Consequently, institutions have explicit and implicit policies that ensure their survival. If an organization's overt and covert policies, which define the scope of its actions and agency, conflict with the organization's fundamental goals that shape its philosophy and nature, the organization will fail to meet visitors' expectations, thereby eroding institutional trust. This level of institutional distrust does not stem from the actions of individual agents, but rather from structural factors. Unfortunately, in most cases, visitors are unaware of these institutional constraints and attribute their dissatisfaction to the staff and intermediaries of the organization. In reality, these intermediaries operate within the confines of the organizational structure, having limited authority, decision-making power, and agency.Therefore, it could be inferred that the erosion of institutional trust was not solely influenced by the performance of agents within welfare and supportive institutions, with whom workers directly interacted, but also stemmed from covert and hidden policies that influenced the organization's performance, often remaining concealed from visitors.